Proteína e gordura do leite captado em Minas Gerais e Goiânia entre 2003 e 2006 - Antônio Mourthe Neto (2008)
With the intent to create a production profile and observe the changes that took place in the nutritional quality of the milk produced in Minas Gerais and Goiânia after the institution of Instrução Normativa 51 and milk quality payment, this study was conducted. The data, a total of 303.070 data collected from 32 dairy cooperatives and about 7.365 dairy producers, in the period between January 2003 and December 2006, was analyzed for the content of milk fat and protein. The analysis indicated an average of 3,22% for protein and 3,70% for fat during this period. These values varied 0,2 percentage points on average throughout the months of the year, this variation being associated with changes in diet. It wasn’t observed any expressive modifications in these values after the beginning of milk quality payment in July 2005, with only 15,97% of producers reaching maximum paymente for protein and 0,89% for fat content.